2012
DOI: 10.1007/s00234-012-1042-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of microstructural maturational changes of the corpus callosum in preterm and full-term children: a diffusion tensor imaging study

Abstract: The present study shows that thinning of the CC is correlated with lower FA value and that it is more pronounced in preterm children. In addition, the isthmus was found to be the most vulnerable subdivision in preterm children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
6
19
0
Order By: Relevance
“…In our VPT sample we observed greater diffusion and reduced volume, indicating there may be either impairment or delayed development in the white matter tracts of the VPT brain. These findings are consistent with other studies of preterm cohorts that have reported altered microstructural organization in numerous white matter tracts, compared with term-born controls (Nagy et al , 2003, Skranes et al , 2007, Constable et al , 2008, Mullen et al , 2011, Jo et al , 2012, Lee et al , 2013). …”
Section: 4 Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our VPT sample we observed greater diffusion and reduced volume, indicating there may be either impairment or delayed development in the white matter tracts of the VPT brain. These findings are consistent with other studies of preterm cohorts that have reported altered microstructural organization in numerous white matter tracts, compared with term-born controls (Nagy et al , 2003, Skranes et al , 2007, Constable et al , 2008, Mullen et al , 2011, Jo et al , 2012, Lee et al , 2013). …”
Section: 4 Discussionsupporting
confidence: 92%
“…Studies also show abnormal microstructural organization in a number of white matter pathways in the preterm brain, including the internal capsule, external capsule, inferior fronto-occipital fasciculus, uncinate fasciculus, superior longitudinal fasciculus, inferior longitudinal fasciculus, centrum semiovale (Nagy et al , 2003, Skranes et al , 2007, Constable et al , 2008, Mullen et al , 2011, Jo et al , 2012, Lee et al , 2013, Groeschel et al , 2014), and corpus callosum (Thompson et al , 2014), which has previously been reported for the current cohort. dMRI studies exploring structure-function associations in preterm cohorts have found that alterations in white matter microstructure are related to motor deficits (Skranes et al , 2007, Counsell et al , 2008, Rose et al , 2009, Thompson et al , 2012, van Kooij et al , 2012, Northam et al , 2012 ), neurosensory impairments (Bassi et al , 2008, Berman et al , 2009, Reiman et al , 2009, Glass et al , 2010, Groppo et al , 2014), and behavioral dysfunction (Nagy et al , 2003, Skranes et al , 2007, Rogers et al , 2012).…”
Section: 1 Introductionsupporting
confidence: 85%
“…Other studies about CC compared preterm and term children with neuroimaging, but the timings of scanning were after a significant postnatal period [3] , [39] , [40] , [50] [52] . These studies consistently report reduced CC in premature children [3] , [39] , [50] , [51] in comparison to nearly preterm or term born infants [3] , [40] . However, the multiple confounders that influence postnatal brain maturation in the time between birth and imaging comprise the ability to directly associate gestational age at birth to in utero brain development.…”
Section: Discussionmentioning
confidence: 72%
“…Tractography studies also find associations between perinatal diffusion measures and clinical outcomes [ 7 , 16 , 44 , 47 52 ] and FA increases with increasing gestational age [ 51 ]. Group differences in diffusion properties of white matter in preterm compared to full term samples have also been investigated in older children [ 9 , 10 , 12 ] and adolescents [ 11 , 13 ]. These structural studies have generally observed decreased mean FA of white matter tracts in the preterm sample compared to the full term sample [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%